2015
DOI: 10.1155/2015/389234
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength of MDP-Containing Self-Adhesive Resin Cement and Y-TZP Ceramics: Effect of Phosphate Monomer-Containing Primers

Abstract: Purpose. This study was conducted to evaluate the effects of different phosphate monomer-containing primers on the shear bond strength between yttria-tetragonal zirconia polycrystal (Y-TZP) ceramics and MDP-containing self-adhesive resin cement. Materials and Methods. Y-TZP ceramic surfaces were ground flat with #600-grit SiC paper and divided into six groups (n = 10). They were treated as follows: untreated (control), Metal/Zirconia Primer, Z-PRIME Plus, air abrasion, Metal/Zirconia Primer with air abrasion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
73
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(89 citation statements)
references
References 22 publications
5
73
1
10
Order By: Relevance
“…Many studies have reported that sandblasting combined with phosphate ester monomers containing agents provides good bond strength to zirconia . The results of the this study are in agreement.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Many studies have reported that sandblasting combined with phosphate ester monomers containing agents provides good bond strength to zirconia . The results of the this study are in agreement.…”
Section: Discussionsupporting
confidence: 89%
“…The MDP molecule contains a phosphate ester group, which chemically bonds to metal oxides, and a methacrylate group, which bonds to the resin matrix of the resin cement . The positive impact of using such materials is well‐established in the literature …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the surface of zirconia that has been coated with a 10-methacryloyloxydecyl dihydrogen phosphate (MDP)-containing silane primer after sandblasting is more effective at providing chemical and micro-mechanical bond strength with the tooth structure [8]. Silane or MDP-containing silane primer treatments improve the chemical bond strength of zirconia [9].…”
Section: Introductionmentioning
confidence: 99%
“…Bonding of phosphate ester monomers to Y-TZP purportedly involves a silane-like coupling mechanism based on hydroxylation-driven chemistry1. Because phosphate ester monomers can also adhere to tooth structures via a predominantly chemical bonding mechanism678, they are increasingly being used for developing phosphate ester monomer containing primers, adhesives and resin-based cements for luting Y-TZP ceramic restorations to tooth structures.…”
mentioning
confidence: 99%